1992
DOI: 10.1002/bit.260401007
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient‐dependent selection of morphological mutants ofFusarium graminearumA3/5 isolated from long‐term continuous flow cultures

Abstract: Highly branched (colonial) mutants (MC1-1-, CC1-1, and C106) of Fusarium graminearum A3/5 were each grown with the parental strain (A3/5) in continuous flow cultures at high and low dilution rates using a variety of nutrient limitations. MC1-1 replaced A3/5 in all nutrient-limited cultures tested (glucose-, Mg(2+)-, ammonium-, and sulphate-limited cultures), suggesting that it has a higher maximum specific growh rate than A3/5. Compared with A3/5, C106 was positively selected for in Mg(2+)-limited cultures and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…It is known that increased branching is part of a pleiotropic response to altered enzyme activity in glucose-6-P dehydrogenase and phosphoglucomutase mutants of Neurospora crassa Tatum, 1966, 1967) and pleiotropic effects are also implicated in the highly branched mutants isolated from F. venenatum fermentations (Wiebe et al, 1992). However, improved culture rheology, rather than improved secretion or production, Figure 6.…”
Section: Discussionmentioning
confidence: 96%
“…It is known that increased branching is part of a pleiotropic response to altered enzyme activity in glucose-6-P dehydrogenase and phosphoglucomutase mutants of Neurospora crassa Tatum, 1966, 1967) and pleiotropic effects are also implicated in the highly branched mutants isolated from F. venenatum fermentations (Wiebe et al, 1992). However, improved culture rheology, rather than improved secretion or production, Figure 6.…”
Section: Discussionmentioning
confidence: 96%
“…3). However, as the selection coefficient of A28-S relative to A3/5 actually became (Wiebe et al, 1992).…”
Section: Discussionmentioning
confidence: 98%
“…Thus, increased hyphal branching does not appear to be associated with selective advantages of mutants selected at low dilution rates in glucose-limited chemostat cultures of F. graminearam. Wiebe et al (1992) showed that a mutation in an enzyme of the pentose phosphate pathway in F. graminearam A3/5 resulted in a colonial mutant with a selective advantage in glucose-limited cultures at high dilution rates. The present results suggest that strain A28-S had an altered carbon metabolism as well as an improved glucose transport system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations